Exploring Agroforestry Systems and Their Practitioners in Mid Hills of Nepal - Magar, Lilu Kumari; Kafle, Gandhiv (Journal of Agriculture and Forestry University, 2025)
Farmers of Nepal have a long history of integrating agriculture and forestry in the same piece of land as agroforestry (AF). Farmers of different socioeconomic characteristics have practiced different agro-ecological practices on their farmlands. This research was carried out in Raksirang Rural Municipality of Makawanpur District in the mid-hill region of Nepal, to explore major AF systems and determine the characteristics associated with farmers' adoption decisions. Data were collected using direct observation and different social survey techniques: household survey (n=80), focus group discussions (n=2) and key informant interviews (n=9). Two types of AF systems were found to be adopted at the study site, i.e., farm-based and forest-based. Agri-silviculture, agri-silvipasture and home gardening were commonly practiced systems. Landholding size, literacy rate, involvement in leasehold forest and provision of training are the major factors affecting the adoption of the AF system. There was no significant relation between the livestock unit and cast with the adoption of an agroforestry system. In-depth studies on the dynamism of agroforestry systems are recommended.